Preliminary normative data for adult English first and second language speakers in South Africa on the "RSA low linguistically loaded central auditory processing test battery" - Campbell, Nicole Githa (University of Pretoria, 2024)
Dissertation (MCommunication Pathology)--University of Pretoria, 2002.